They led the way : 14 American women - Johnston, Johanna; Hollinger, Deanne (New York : Scholastic, 1973)
Portraits of fourteen American women determined to use their talents despite the difficulties encountered in getting into careers reserved exclusively for men.
790
Accelerated Reader AR
Keywords: Women -- Biography